Influence of geometry on the flexural strength of plastic gears - Moya Rodríguez, Jorge Laureano (2012)
In this paper we can examine the influence of geometric changes in the straight tooth profiles of cylindrical plastic gears on its bending resistance by the finite element method and its influence on the resistance to bending. The main objective of the study is to develop a procedure to determine the influence of asymmetry and the teeth modification with regard to the flexural strength of the plastic gear teeth. In this study we have calculated the tooth bending stresses using mathematical procedures and use of software that has allowed to increase the flexural strength due to the teeth modification (by a modification factor from 0 to 0,7) and also determine the shape factor for the cylindrical asymmetrical straight teeth gears, and which constitutes a scientific innovation. The results obtained satisfy the general and specific objectives of the study, which demonstrates that innovations will contribute to the industry and the country technological development.